Answer:
m=2, n=-1 or (2,-1)
Step-by-step explanation:
Hi there!
We're given this system of equations:
3n+5m=7
m-4n=6
we want to solve by substitution; in one equation, we'll set one variable to equal an expression containing the other variable, substitute that expression as the variable into the other equation, solve for the variable substituted, and use the value of that variable to find the other variable
First, let's get the expression we'll substitute into the other
let's use m-4n=6 as it has 1m (m by itself)
add 4n to both sides
m=4n+6
now substitute 4n+6 as m into 3n+5m=7 to solve for n
3n+5(4n+6)=7
do the distributive property
3n+20n+30=7
combine like terms
23n+30=7
subtract 30 from both sides
23n=-23
divide both sides by 23
n=-1
we found the value of n
now let's substitute -1 as n in m=4n+6 to find the value of m
m=4(-1)+6
multiply
m=-4+6
add
m=2
so the answer is m=2, n=-1. As a point, it's (2,-1)
Hope this helps! :)